Mucormycosis Research: A global outlook through bibliometric approaches - Ram, Shri; Sharma, Hemant; Rai, Arun Kumar (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. Mucormycosis is a fungal infection in humans where the causative pathogens belong to the order of Mucorales. The fungal pathogens are also known as black fungi based on morphological characteristics. Mucormycosis is increasingly observed in patients suffering from the COVID-19 virus from different states of India, wherein steroids are being used as standard therapy. The prevalence of coronavirus disease and the infection by the black fungus (Mucormycosis) poses several challenges to its mitigation. The purpose of the study is to analyze the research trends of mucormycosis using bibliometric methods. Design/Methodology/approach. The study utilizes standard bibliometric methods to analyze bibliographic literature on Mucormycosis retrieved from the SCOPUS database. All keywords (MeSH terms) associated with Mucormycosis were used to frame a search query and retrieve bibliographic data from the database. The bibliometric indicators were used to assess research productivity in mucormycosis for publication growth; subject distribution; productive authors, institutes, and countries; journals, highly cited articles; and hot spots and research progress based on the keyword analysis. VOSviewer network visualization tools have been used for mapping research. Results/Discussion. The analysis of 25,251 bibliographic records shows exponential growth in literature during seventy years. Though mucormycosis research is spread across the globe, the prevalence of the study is widespread in the South-East Asian region. Author keyword analysis shows that the research focuses on the medical subject and expands into multidisciplinary research areas. Conclusion. Bibliometrics always provides insight into the research progress in any field or topic of study. This study provides insight into research progress in Mucormycosis. The researcher may use the results to analyze different areas of mucormycosis and utilize the key concepts for further research, especially researching better clinical practices and drug developments. Originality/Value. Through this paper, it is quite clear that the appearance of research contribution on mucormycosis coupled with COVID-19 has opened a new direction of research that clinical researchers take up in future research.